ANALISIS KEBIJAKAN PEMBANGUNAN HUKUM NASIONAL BERDASARKAN UU NO. 25 TAHUN 2004 TENTANG SISTEM PERENCANAAN PEMBANGUNAN NASIONAL - Halim, Abd. (Al-Mazaahib: Jurnal Perbandingan Hukum, 2014)
This article explains the fundamental differences of national law development based on Act No. 25/2004 about National Development Planning System.In the period before the birth of Act No. 25 /2004, political interests at that time mistakenly putting the function of law as a tool of social engineering. Law simply used as legitimacy by policy makers, the emphasis tends to the law development in both the normative and empirical level and placement by per field and sector in Guidelines of State Policy, whereas in Act No. 25 2004, law development more oriented towards regulative framework (normative) and the placement does not sectorally / per field.